2022
DOI: 10.26508/lsa.202201497
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of a membrane receptor that binds to human STC1

Abstract: Stanniocalcin-1 (STC1) is a hypocalcemic hormone originally identified in bony fishes. The mammalian homolog is found to be involved in inflammation and carcinogenesis, among other physiological functions. In this study, we used the TriCEPS-based ligand–receptor methodology to identify the putative binding proteins of human STC1 (hSTC1) in the human leukemia monocytic cell line, ThP-1. LC–MS/MS analysis of peptides from shortlisted hSTC1-binding proteins detected 32 peptides that belong to IGF2/MPRI. Surface p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Recently, several clinicopathological studies have identi ed serum STC2 levels are elevated in patients with HCC, gastric cancer and colorectal cancer, and particularly high serum STC2 levels are associated with poor prognosis 20,50,51,52 , indicating secreted STC2 could perform its biological functions through an endocrine mechanism at organism levels. It has been reported that the cation-independent mannose-6-phosphate receptor/IGF2R interacts with STC1 and may serve as a receptor 53 . Whether STC2 shares the same receptor or uses a different surface protein as a receptor remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several clinicopathological studies have identi ed serum STC2 levels are elevated in patients with HCC, gastric cancer and colorectal cancer, and particularly high serum STC2 levels are associated with poor prognosis 20,50,51,52 , indicating secreted STC2 could perform its biological functions through an endocrine mechanism at organism levels. It has been reported that the cation-independent mannose-6-phosphate receptor/IGF2R interacts with STC1 and may serve as a receptor 53 . Whether STC2 shares the same receptor or uses a different surface protein as a receptor remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31] In the mitochondria, megalin is found in association with Sirt3 and Stc1. [29] Stc1 receptors are found at the plasma membrane and inner mitochondrial membrane, [30,32,33] and as discussed above, Stc1 is defined as mitochondrial intracrine. [6] In prior publications, we showed Stc1 upregulates mitochondrial uncoupling proteins (UCPs) [34][35][36][37] and the energy sensor Sirt3 through activation of yet another energy sensor, AMP-activated protein kinase (AMPK).…”
Section: Megalin Shuttles Mitochondrial Intracrinesmentioning
confidence: 99%